Hiding in plain sight: communication theory in implementation science - Manojlovich, Milisa; Squires, Janet E; Davies, Barbara; Graham, Ian D (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Poor communication among healthcare professionals is a pressing problem, contributing to widespread barriers to patient safety. The word “communication” means to share or make common. In the literature, two communication paradigms dominate: (1) communication as a transactional process responsible for information exchange, and (2) communication as a transformational process responsible for causing change. Implementation science has focused on information exchange attributes while largely ignoring transformational attributes of communication. In this paper, we debate the merits of encompassing both paradigms. Discussion We conducted a two-staged literature review searching for the concept of communication in implementation science to understand how communication is conceptualized. Twenty-seven theories, models, or frameworks were identified; only Rogers’ Diffusion of Innovations theory provides a definition of communication and includes both communication paradigms. Most models (notable exceptions include Diffusion of Innovations, The Ottawa Model of Research Use, and Normalization Process Theory) describe communication as a transactional process. But thinking of communication solely as information transfer or exchange misrepresents reality. We recommend that implementation science theories (1) propose and test the concept of shared understanding when describing communication, (2) acknowledge that communication is multi-layered, identify at least a few layers, and posit how identified layers might affect the development of shared understanding, (3) acknowledge that communication occurs in a social context, providing a frame of reference for both individuals and groups, (4) acknowledge the unpredictability of communication (and healthcare processes in general), and (5) engage with and draw on work done by communication theorists. Summary Implementation science literature has conceptualized communication as a transactional process (when communication has been mentioned at all), thereby ignoring a key contributor to implementation intervention success. When conceptualized as a transformational process, the focus of communication moves to shared understanding and is grounded in human interactions and the way we go about constructing knowledge. Instead of hiding in plain sight, we suggest explicitly acknowledging the role that communication plays in our implementation efforts. By using both paradigms, we can investigate when communication facilitates implementation, when it does not, and how to improve it so that our implementation and clinical interventions are embraced by clinicians and patients alike.